Addressing Anxiety Problems in Hospital Patients with Guided Imagery Therapy: A Systematic Review - Sulistiyawati, Sri; Muhith, Abdul; Mahyuvi, Tata (Chakra Brahmanda Lentera Institute, 2024)
Background: Anxiety problems are often experienced by patients in hospitals due to various factors, such as medical conditions, medical procedures, or unfamiliar environments. One of the non-pharmacological interventions that has been widely studied to manage anxiety is guided imagery therapy. Objective: This systematic review aims to evaluate the effectiveness of guided imagery therapy in addressing anxiety problems in hospital patients. Methods: Literature searches were conducted on databases such as Google Scholar, Science Direct, and Pubmed. Article searches were carried out systematically from 2019-2024 using severalkeywords, namely